PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT PAGAR MERBAU - Dimas Tito Wicaksana; Muhammad Prasetyo Wibowo; Syafrizal (STKIP Subang, 2026)
This research was conducted to find out how communication and organizational culture affect employee performance. And this research uses a quantitative method with a research place at the Pagar Merbau Sub-district office. The sampling technique uses saturated samples, namely the entire population is the number used as a sample, which is as many as 36 employees. Then the data collection technique by distributing questionnaires or questionnaires and the technique of using data analysis using multiple linear analysis, classical assumptions, hypothesis tests and determinant coefficients. The RSquare value (r2) is 72.7% and uses the help of IBM SPSS version 26 software application data processing. The results of this study showed that partially in the communication obtained a tcal < ttable (1,580 <2,034) and a significance value of 0.124 >0.05 with the conclusion that the communication partially had no significant influence on employee performance and organizational culture partially obtained a tcal > ttable (5,873 > 2,034) and a significance value of 0.000<0.05 as a result, organizational culture had an influence and significance on performance, and obtained the value of Fcalcul> Ftabel (43.879 >3.28) and a significance value of 0.000 < 0.05 with the conclusion that communication and organizational culture are influential and significant on performance.